Genetic variability, correlation and path analysis for yield and yield components in promising rice (Oryza sativa L.) genotypes (SAARC Journal of Agriculture, 2015)
Seventy three rice varieties were evaluated for their variability with regards to yield and yield components. Estimates of heritability and genetic advance in per cent of mean were also obtained for the above traits. In addition, studies on character associations and path coefficients were also undertaken. The results revealed high variability, heritability and genetic advance in per cent of mean for grain yield while panicle bearing tillers and 1000 grain weight had recorded high heritability coupled with low genetic advance as per cent of mean. Further, yield was observed to be positively associated with panicle bearing tillers and number of filled grains per panicle and these characters were noticed to exert high direct effects on grain yield per plant. High indirect effects of most of the traits were noticed mostly through panicle bearing tillers per hill indicating importance of the trait as selection criteria in crop yield improvement programmes.SAARC J. Agri., 13(1): 99-108 (2015)